Effect of a Bacterial Consortium on Passivation Property of 2024 Aluminum Alloy - Paez-Collio, M; Paez-Collio, M; Muñoz-Moena, L; Muñoz-Moena, L; Blamey-Alegria, J (Electrochemical Science Group, 2019)
A bacterial consortium was recollected from corrosion products formed on a vertical fin of a military helicopter exposed to Antarctic environment for 4 years. For the identification and characterization of the consortium, DNA sequencing was performed showing that the consortium was mainly composed by three strains. Two of the strains showed a close affiliation to Bacillus toyonensis and Staphylococcus aureus. However, the third strain studied did not show affiliation by 16S rRNA analysis to any genus so far described. Additionally, morphological and electrochemical studies of an aluminum 2024-T3 alloy prior and after exposure to a sterile and inoculated minimal salt medium at 4 °C were carried out by using scanning electron microscope, open circuit potential and electrochemical impedance spectroscopy. The experimental results revealed that steady-state properties of the passive film were modified by the bacterial consortium and isolates. © 2019 The Authors.